Nationalism and Xenophobia in Post-Soviet Russia: Skinhead and Nashi Movements - MIRON, Ioana Mădălina (2026)
This volume situates these movements within a longer historical trajectory of Russian nationalism. From the Tsarist doctrine of “Orthodoxy, Autocracy, and Nationality” to Soviet patriotism and post-1991 identity struggles, Russian political culture has repeatedly reconfigured the relationship between state, nation, and people. The revival of imperial symbols, the rehabilitation of selective historical narratives, and the persistent emphasis on spiritual and civilisational uniqueness have provided fertile ground for the resurgence of nationalist discourse. In this context, youth movements become particularly significant: they are both products of their time and laboratories for the future.